Walter W. Piegorsch and A. John Bailer (2005): Analyzing environmental data : Wiley & Sons, xv + 496 pp., US $ 90.00, GB £ 45.00, e 67.99, ISBN 0470848367 - Maronna, Ricardo Antonio (2010)
This book covers an impressive range of topics. Chapter 1 deals with simple and multiple linear regression and ANOVA. Chapter 2 contains detailed discussions of several simple nonlinear regression models. Chapter 3 presents likelihood and quasi-likelihood estimation for GLIM, and discusses different models for counts data. Chapter 4 deals with the estimation of median effective dose, risk estimation, and benchmark, uncertainty and sensitivity analyses. Chapter 5 considers harmonic regression, ARIMA models, intervention analysis and growth curves. Chapter 6 presents distance methods for spatial data, semivariograms, and diverse variants of kriging. Chapter 7 considers mainly meta-analysis and historical control information. Chapter 8 begins with a survey of basic sampling techniques, and then discusses specialized environmental methods such as capture-recapture, quadrat and line-intercept designs.